: Abstrak - Paulus Tangke; Gracia E. Lauren; Anthony Holly; Robert Jao (Jurnal Ilmiah Akuntansi Peradaban, 2022)
This study aims to investigate the moderating role of corporate governance on the effect of financial distress on tax avoidance. The theory used in this study is agency theory. This study uses secondary data obtained by using documentation method. Data source in this research is the annual reports of property and real estate sector companies listed on the Indonesia Stock Exchange in the 2018-2020 period. The method used for data analysis is moderated regression analysis. The result of this research indicate that financial distress has a positive and significant effect on tax avoidance. Furthermore, corporate governance proxied by independent commisioners can moderate the effect of financial distress on tax avoidance. Keyword: Financial Distress, Tax Avoidance, Corporate Governance